Argentina : Staff Report for the 2000 Article IV Consultation, First Review Under the Stand-By Arrangement, and Request for Modification of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In 1999, the economy of Argentina was affected owing to recession. More than half of the external account deficit was financed by net foreign direct investment. The public finances deteriorated in 1999, reflecting the impact of the recession on tax revenue, a weakening of tax compliance, a growing interest bill, and spending overruns at both the federal and the provincial government level. The banking system has weathered well the recession, and strong prudential defences that characterize the Argentine banking system have been maintained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet